Finding New Paths for Growth in Djibouti - Benyagoub, Mehdi (World Bank, Washington, DC, 2014)
The report posits a long-term vision for Djibouti s economic development with specific measures that form a road map for long term, sustainable growth. The current growth model is highly capital intensive and dependent on rent-seeking, thus presenting sustainability and diversification challenges. Growth has increased recently, reaching 4.6 percent on average between 2005 and 2010. Also, recent growth is tightly linked to strong inflows of foreign investment, financing the new port and hotel infrastructure. These investments are due to Djibouti s strategic geographic location at the entrance to the Red Sea, owing to the presence of foreign military bases and its status as Ethiopia s sole means of access to the sea. Historically the government has played an important role in Djibouti s economy but with today s fiscal constraints, growing the private sector is the only way to sustain and promote growth, provide jobs, and reduce poverty. The private sector remains very small and not well organized.